Biofilm formation and molecular analysis of intercellular adhesion gene cluster (icaABCD) among Staphylococcus aureus strains isolated from children with adenoiditis - Ghaioumy, Rasoul; Tabatabaeifar, Fatemehalsadat; Mozafarinia, Karamat; Arabi Mianroodi, Aliasghar; Isaei, Elham; Morones Ramírez, José Rubén; Agha Kuchak Afshari, Setareh; Kalantar Neyestanaki, Davood (Tehran University of Medical Sciences, 2021)
Background and Objectives: It is well known that Staphylococcus aureus biofilm plays an important role in adenoiditis and biofilm resistance frequently results in failure of therapy. The goal of this study was to evaluate the biofilm production of S. aureus isolates obtained from adenoid specimens and assess the relationship between biofilm formation ability and ica operon genes. Materials and Methods: A total of 112 adenoid samples were obtained from patients under 15 years old with adenoid hypertrophy. All S. aureus isolates were initially identified by standard microbiological tests and amplification of nuc by polymerase chain reaction (PCR) technique. Biofilm formation of S. aureus isolates was evaluated and icaADBC genes were detected by PCR technique. Results: There were 46 isolates (41%) identified as S. aureus. The ability to produce biofilm was detected among total S. aureus isolates. Molecular study of ica operon revealed that 2 (6.3%) and 19 (59.4%) isolates carried icaA and icaD, respectively. The prevalence of icaA + icaD was seen among 11 (34.4%) S. aureus isolates, while icaC and icaB were not detected. Conclusion: Our findings indicated that icaABCD operon are associated with biofilm formation in S. aureus isolates, however the absence of these genes may not necessarily exclude this property.